Bibliografía española de las Ciencias de la Información (Julio-Diciembre 1981) - García Gutiérrez, Antonio L.; Martín Martín, Fernando; Valle Gastaminza, Félix del (Documentación de las Ciencias de la Información, 1982)
Sin resumen